Dual Effects of Cellular Immunotherapy in Inhibition of Virus Replication and Prolongation of Survival in HCV-Positive Hepatocellular Carcinoma Patients. (16th March 2016) - Qian, Lei; Wang, Nanya; Tian, Huimin; Jin, Haofan; Zhao, Hengjun; Niu, Chao; He, Hua; Ge, Tingwen; Han, Wei; Hu, Jifan; Li, Dan; Han, Fujun; et al.
Abstract : Immune cells play an important role in the development and progression of hepatitis C virus (HCV) and hepatocellular carcinoma (HCC). We conducted a retrospective study to evaluate the influence of adoptive cellular immunotherapy (CIT) on viral load and progression-free survival (PFS) for HCC patients infected with HCV. Patients (n = 104 ) were divided into a control group (conventional therapy, n = 73 ) and study group (combination of CIT and conventional therapy, n = 31 ). Autologous mononuclear cells were induced into natural killer, γδ T, and cytokine-induced killer cells and infused intravenously to study group patients. More patients had shown viral load decrease or were stable in study group (100% versus 75%) (p = 0.014 ). The median PFS of the study group and control group was 16 and 10 months, respectively (p = 0.0041 ), and only CIT was an independent prognostic factor for PFS (hazard ratio, 0.422; p = 0.005 ). Three patients developed transient moderate fever after infusion, and there were no significant differences in alanine aminotransferase and aspartate aminotransferase levels before and after treatment in both groups. Our results show that CIT contributes to improvement of prognosis and inhibition of viral replication in HCV-related HCC patients, without impairment of liver function.